ASSIMILATION OF THE ROUND WITH DIAMETER 160 MM IN CONDITIONS OF MILL 850 AT RUP “BMZ” - M. A. Murikov; P. K. Gribovski; V. A. Politov; V. V. Gordienko; O. V. Rjabtsev (Литьë и металлургия, 2007)
The developed temperature regimes of metal heating, energy-power and temperature parameters of rolling provided receiving of geometrical sizes, mechanical and metallographic investigations of hot-rolled round rolled metal with diameter 160 mm.